Public Participation in the Budget Process in the Republic of Korea - Kang, Young Kyu (World Bank, Washington, DC, 2018)
In January 2013, the International Budget Partnership (IBP) released the latest Open Budget Survey (OBS) with a new section on public participation. The survey results are not encouraging. For the 100 surveyed countries, the average score for public participation in the budget process is 19 out of 100. However, one country stands out. With a score of 92, Korea emerges as the only country ‘that provides extensive opportunities for public engagement’ (IBP 2012, 33). What makes Korea an exception? This note investigates the different public participation mechanisms in Korea and illustrates how public inputs are reflected in the country’s budget process and fiscal policies.